2008
DOI: 10.1016/j.biocon.2008.06.027
|View full text |Cite
|
Sign up to set email alerts
|

Examining conservation attitudes, perspectives, and challenges in India

Abstract: as conservation foci, and on specific policy initiatives are common among Indian and global conservationists. We surveyed Indian conservationists about the conservation effectiveness of protected areas and charismatic species, as well as status of conservation and research efforts. We expected differences among people based on professional affiliation, and educational background. We examined participants' opinions on conservation policies like Project Tiger and Elephant, the Forest Rights Act, and the Tiger Ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(37 citation statements)
references
References 22 publications
1
35
1
Order By: Relevance
“…In contrast to other studies that identify education, work environment, and age as important predictors of conservationists' attitudes (Karanth et al 2008), this study found that answers to questionnaire items did not vary significantly by gender, age, institutional affiliation, level of education, degree type, area of specialization, or years of professional experience. This finding is interesting as it suggests that the views of project supervisors are may be shaped by factors that are not specific to any particular demographic group.…”
Section: Discussioncontrasting
confidence: 78%
See 2 more Smart Citations
“…In contrast to other studies that identify education, work environment, and age as important predictors of conservationists' attitudes (Karanth et al 2008), this study found that answers to questionnaire items did not vary significantly by gender, age, institutional affiliation, level of education, degree type, area of specialization, or years of professional experience. This finding is interesting as it suggests that the views of project supervisors are may be shaped by factors that are not specific to any particular demographic group.…”
Section: Discussioncontrasting
confidence: 78%
“…Other studies have contrasted the attitudes held about wildlife between wildlife agency managers and members of the public (Peyton and Langenau 1985;Kennedy 1985;Carr and Tate 1991;Bjerke et al 1998;Kaltenborn et al 1999;Koval and Mertig 2004). At least one study assesses conservation professionals' attitudes about the use of participatory approaches to wildlife conservation in India (Karanth et al 2008). However, few if any studies have examined the views of wildlife conservation professionals about the role of gender in community-oriented conservation.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Globally, policy makers heavily depend on establishing protected areas to conserve forest resources [63,64], even though effectiveness of protected areas in conserving biodiversity has been questioned [44]. However, in India, it is generally agreed that protected areas are working in reducing deforestation [44,65]. This negative correlation between deforestation and BNP, Talli and Bilikal Reserve Forest throws light on the underlying driving factor of policy measures at the national level (establishing protected areas) and its impact on local level land-cover changes, here deforestation.…”
Section: Discussionmentioning
confidence: 99%
“…: some people might not have been registered or included in the catalogue. The work presented here used a similar approach that was successfully employed by Karanth et al (2008) to analyze conservation attitudes and perspectives in India, based on a survey.…”
Section: Validity Of Materials and Methodsmentioning
confidence: 99%